2019
DOI: 10.1097/tp.0000000000002280
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Temperature and Oxygen Supports Long-term Culture of Human Islets

Abstract: By optimizing temperature and oxygen concentration, we cultured human islets for 2 weeks with minimal loss of volume and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…It is also associated with a loss of beta cells but not with a reduction in their percentage [22], and it can be used to combine preparations if quantitative criteria are not immediately met, while preserving the desired metabolic effect in patients [8]. However, since beta cell recovery after culture may be influenced by many confounders [22,25,26], the measurement of beta cells after purification was used to examine if DCD III organs are suitable for the preparation of islet cell grafts. Islet mass serves since long as a criterium to select pancreatic islet isolates for clinical transplantation [1,6,15].…”
Section: Discussionmentioning
confidence: 99%
“…It is also associated with a loss of beta cells but not with a reduction in their percentage [22], and it can be used to combine preparations if quantitative criteria are not immediately met, while preserving the desired metabolic effect in patients [8]. However, since beta cell recovery after culture may be influenced by many confounders [22,25,26], the measurement of beta cells after purification was used to examine if DCD III organs are suitable for the preparation of islet cell grafts. Islet mass serves since long as a criterium to select pancreatic islet isolates for clinical transplantation [1,6,15].…”
Section: Discussionmentioning
confidence: 99%
“…This explains why viability-conventional is overestimated compared to viability-semi-automated in islet batches containing large islets. Automated viability determination has recently been applied with success in various studies 10 , 16 . In addition to being a resourceful tool for assessing islet viability, a similar automated method has been developed to evaluate islet purity using zinc-chelating DTZ staining 24 , 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Nonobese diabetic, severe combined immunodeficiency mice (Charles River Laboratories, Wilmington, MA, USA) were used as recipients for islet transplantations, as previously described 16 . Mice were rendered diabetic by streptozotocin injections (50 mg/kg, intraperitoneal injections in consecutive 3 d).…”
Section: Methodsmentioning
confidence: 99%
“…However, isolated islets were stressed, and islet function was impaired during the in vitro cultivation period, which may result in unsatisfactory transplant outcomes. Various efforts have been made to preserve islet mass and function before transplantation, including supplementation of additives like green tea extract ( 48 ) and liraglutide ( 49 ); use of scaffolds or extracellular matrix ( 50 52 ), and modulation of the culture temperature and gas environment ( 53 , 54 ). To the best of our knowledge, this is the first study that demonstrated how using human amniotic membrane extract as medium supplementation to improve islet viability and function.…”
Section: Discussionmentioning
confidence: 99%